Knowledge and Will: An Explorative Study on the Implementation of School-Wide Positive Behavior Support in Sweden - Nylén, Kata; Karlberg, Martin; Klang, Nina; Ogden, Terje (Frontiers in Psychology, 2021)
School-wide positive behavior support (SWPBIS) is a well-evaluated school approach to promoting a positive school climate and decreasing problem behaviors. Initial implementation is one of the most critical stages of program implementation. In this qualitative study, the initial implementation of SWPBIS in Swedish schools was studied using an implementation model of behavior change as guidance for interviews and analyses. The study makes significant contributions to previous research as little is known of the implementation of SWPBIS in Swedish context. Focus-group interviews were conducted with 59 professionals on implementation teams from nine schools. Themes were extracted according to implementation team members' perceptions and descriptions of how the initial implementation was carried out. The results of this study revealed relevant themes within the three domains of Capability, Opportunity, and Motivation. Core features were found under the themes of knowledge and experience of similar evidence-based programs, process or result orientation, time, manual content, organizational prerequisites, team functioning, implementation leadership, program as a unifying factor, program aligning with staff beliefs, plausible expectations, and emotional reinforcement. Results are discussed in terms of how they can be used in continuing to develop the Swedish model of SWPBIS. Implications regarding implementation in Swedish schools are discussed, as is the applicability of the model of behavior change for studying implementation in schools.